2020
DOI: 10.1002/rth2.12416
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of diagnosing heparin‐induced thrombocytopenia in patients with COVID‐19

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 3 publications
0
18
0
4
Order By: Relevance
“…To date, HIT data in SARS-CoV-2-infected patients are scarce, limited to the report of a few HIT cases confirmed using platelet activation assay, and HIT-associated antibody prevalence remains poorly investigated. [3][4][5][6][7][8][9][10][11][12][13] Our prospective cohort study aimed to characterize patients with clinical suspicion of HIT and determine HIT-associated antibody prevalence in hospitalized SARS-CoV-2-infected patients. This study was part of the ICU-COVID and French-COVID cohort registries approved by our institutional ethics committee (IDRCB, 2020-A00256-33; CPP, 11-202020.02.04.68737).…”
mentioning
confidence: 99%
“…To date, HIT data in SARS-CoV-2-infected patients are scarce, limited to the report of a few HIT cases confirmed using platelet activation assay, and HIT-associated antibody prevalence remains poorly investigated. [3][4][5][6][7][8][9][10][11][12][13] Our prospective cohort study aimed to characterize patients with clinical suspicion of HIT and determine HIT-associated antibody prevalence in hospitalized SARS-CoV-2-infected patients. This study was part of the ICU-COVID and French-COVID cohort registries approved by our institutional ethics committee (IDRCB, 2020-A00256-33; CPP, 11-202020.02.04.68737).…”
mentioning
confidence: 99%
“…Several other studies also detected increased PF4/H-reactive antibodies in COVID-19 patients in the context of heparin treatment and patients are suspected of developing "classical" HIT, i.e. heparin exposure-induced HIT [38][39][40][41][42] . A recent randomized trial reported that therapeutic dose of UFH and LMWH did not improve organ dysfunction in critically ill patients with COVID-19 43 .…”
Section: Discussionmentioning
confidence: 88%
“…These ndings were attributed to EIA testing detecting all anti-PF4/Heparin antibodies and the potential for false positive EIAs due to increased in ammation and immunoreactivity in COVID-19, leading to production of anti-PF4/heparin antibodies that are nonpathogenic for HIT. 26 It is unclear how to accurately diagnose HIT in COVID-19 patients due to varying sensitivity and speci city between different EIA and con rmatory tests. 27 Even with our institution's highly sensitive and speci c IgG EIA test, 62.5% patients who were con rmatory testing negative.…”
Section: Discussionmentioning
confidence: 99%